Sposób powstawania, struktura i produkcyjność drzewostanów bukowo-modrzewiowych w Polsce - Andrzejczyk, Tadeusz; Bolibok, Leszek; Drozdowski, Stanisław; Szeligowski, Henryk (Leśne Prace Badawcze, 2011)
The aim of this study was to analyse how the formation processes that generate mixed larch stands with beech in the secondary storey affect their standing volume and growing stock. These estimates were based on data from 19 Polish stands surveyed for age, growth, stand quality and growing stock as partitioned among the tree species and canopy strata. Qualitative traits and changes in the standing volume and growing stock related to the proportion of beech to larch in the stand were analyzed for two larch age groups: (1) less than 120 years old and (2) over 120 years old. The examined stands were generated in two ways: through the establishment of mixed beech-larch crops or through the introduction of beech trees under an existing canopy of larch (usually at aged 40-50 years old or older). The growing stock of large timber in younger stands ranged from 372 to 622 m 3 /ha, including 86 to 190 m 3 /ha from beech and other admixed species, and was 482 to 1102 m 3 /ha from older stands, with species other than larch contributing 158 to 390 m 3 /ha. As the proportion of beech in the stand increases, the overall stand growing stock decreases: to a greater extent in younger than in older stands. Hence, excessive reduction in larch density is not desirable, since it is not compensated by increased beech reaching the upper canopy. In most stands, regardless of the method of stand generation, beech has a high growth rate so adds to stand quality. Stands with the largest growing stock (Młynary i Miłomłym – northern Poland) reached 1034 and 1102 m 3 /ha of large timber, of which the larch standing volume was, respectively 711 and 834 m 3 /ha.